The Effect of Organizational Reputation on E-loyalty: The Roles of E-trust and E-satisfaction - Sadeghi, Amir; Ghujali, Tohid; Bastam, Hadi (ASEAN Marketing Journal, 2021)
Purpose- The purpose of this paper is to examine how effect of Organizational Reputation on E-loyalty with the Roles of E-trust and E-satisfaction. Design/methodology/approach- A quantitative approach was undertaken to analyze. The study used Structural Equation Modelling (SEM) operated by LISREL program to analyze the hypothesis. This paper tests the model by using data from 450 customers of Digikala firm in Iran. Findings- Results indicated that organizational reputation affects e-satisfaction significantly and the impact of organizational reputation on e-trust is significant in the selected population. Originality/value- This study emphasized on the impact of corporate reputation on increasing customer satisfaction, customer trust, and customer loyalty in the electronic commerce company. Hence, this paper investigates the interrelationships between reputation, trust, satisfaction, and loyalty as a unique context.